Study Internalization of Entrepreneurial Values in the Formation of Student Entrepreneurial Character through Scouting Activities - Himawan Sutanto; Rifki Suwaji; Fajriani Azis (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2024)
The purpose of this research is to understand how the Internalization of Entrepreneurial Values can shape Entrepreneurial Character through Student Scouting. The subjects of this study consisted of five members and coaches of the Universitas Negeri Makassar Scout student activity unit, consisting of one coach, two administrators, and two members. This research uses a qualitative approach with a descriptive nature. Sampling was done through non-probability sampling technique, specifically purposive sampling. Data were collected through observations, interviews, and documentation, while data analysis used qualitative analysis methods. Based on the results of the research and discussion, it can be concluded that the internalization of entrepreneurial character through scouting activities includes values such as honesty, discipline, hard work, creativity, innovation, independence, responsibility, cooperation, leadership, perseverance, resilience to risk, commitment, realism, curiosity, communicative, strong motivation to succeed, and action-oriented contained in Scout activities. Some of these activities include practicing the Scout code of honor, achieving general proficiency marks, outdoor activities, deliberations, meetings and briefings, social services, spiritual activities, competitive activities, front cluster ambassadors, seminars and training, and outdoor activities. The internalization of entrepreneurial values in the Universitas Negeri Makassar Scout activity unit in shaping entrepreneurial character has proven to be well implemented. The coach, as an adult figure who directs scouting activities, tries to choose activities and methods to increase the creativity and ability of students in developing entrepreneurial character.